2020
DOI: 10.3390/v12020219
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of PCV3 from Perinatal and Reproductive Cases of PCV3-Associated Disease and In Vivo Characterization of PCV3 Replication in CD/CD Growing Pigs

Abstract: Porcine circovirus 3 (PCV3) has been identified as a putative swine pathogen with a subset of infections resulting in stillborn and mummified fetuses, encephalitis and myocarditis in perinatal, and periarteritis in growing pigs. Three PCV3 isolates were isolated from weak-born piglets or elevated stillborn and mummified fetuses. Full-length genome sequences from different passages and isolates (PCV3a1 ISU27734, PCV3a2 ISU58312, PCV3c ISU44806) were determined using metagenomics sequencing. Virus production in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
100
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(112 citation statements)
references
References 64 publications
10
100
1
1
Order By: Relevance
“…However, the protective role of PCV3-induced antibodies is unknown and different isotypes could have a different role in viral neutralization. Recently, we reported that CD/CD pigs inoculated with virus isolate showed an early IgM but not IgG PCV3-specific response associated with delayed viremia [21]. However, in this study, no detectable IgM (data not shown), but an early and sustained IgG PCV3-specific response was observed.…”
Section: Discussioncontrasting
confidence: 66%
“…However, the protective role of PCV3-induced antibodies is unknown and different isotypes could have a different role in viral neutralization. Recently, we reported that CD/CD pigs inoculated with virus isolate showed an early IgM but not IgG PCV3-specific response associated with delayed viremia [21]. However, in this study, no detectable IgM (data not shown), but an early and sustained IgG PCV3-specific response was observed.…”
Section: Discussioncontrasting
confidence: 66%
“…However, the mere detection of an enzootic virus in animals with clinical conditions is not sufficient to demonstrate its disease causality [ 4 ]. Despite the worldwide ubiquitous distribution of PCV-3 [ 13 , 19 ], there is little evidence of PCV-3 detection within lesions of diseased animals [ 4 , 20 ]. In consequence, it is of great importance to determine the frequency of the virus in farms with reproductive problems and assess its potential causality in these problems.…”
Section: Introductionmentioning
confidence: 99%
“…PCV3 was detected in a coinfection with PCV2 and porcine epidemic diarrhea virus from a severe case of diarrheal disease in China, and the authors reported a triple infection rate of 48.68% (14). PCV3 was first isolated in 2020 in China in perinatal and reproductive sows (15). Therefore, recent reports suggest that more attention should be given to PCV3-associated disease.…”
Section: Introductionmentioning
confidence: 99%